Experimental Wavelet Packet Transient-State Analysis of Electrical Machines Directly Fed by Photovoltaic Cells - (:unkn) unknown (PRAISE WORTHY PRIZE SRL, 2010)
This work describes an experimental wavelet packet transient state analysis for educational purposes The study particularly deals with electrical machines directly fed by photovoltaic cells In a PV system design the selection and proper installation of appropriately-sized components directly affects system reliability, lifetime and initial cost In any installation, one must keep in mind that trade-offs are necessary in system design and component selection In this study the startup and nominal operating behaviors of electrical machines directly connected to a photovoltaic system (not having any storage or control system) were empirically examined The power values obtained (in p u) were decomposed to sub-frequency components by means of the discrete wavelet packet transformation then they were compared to each other Copyright (C) 2010 Praise Worthy Prize S r l - All rights reserved.
Keywords: Photovoltaic Cells; Transient State Electrical Machines Wavelet Filter Bank; Wavelet Packet Transform